"Blue bodies" in a case of cryptogenic fibrosing alveolitis (desquamative type) an ultra-structural study. Issue 6 (December 1978) - Gardiner, I T; Uff, J S
Abstract : A patient with cryptogenic fibrosing alveolitis, with both mural and desquamative features, had two lung biopsies at the times of coronary artery surgery. These lung specimens were studied, using light and electron microscopy, with immunofluorescence techniques and electron microanalysis. In addition to the typical changes of cryptogenic fibrosing alveolitis previously reported, we found "blue-staining bodies" within alveolar macrophages and giant cells. These bodies were 15--25 micrometer in diameter with an iron rich outer rim and core of connective tissue mucin--possibly chondroitin sulphate or dermatan sulphate. It seems unlikely that these "blue bodies" were due to fibreglass dust to which the patients had had a trivial exposure, but their exact nature and significance remains unclear.